Information at work information management in the workplace - Bystöm, Katriina; Heinstrom, Jannica; Ruthven, Ian (Facet Publishing, 2019)
Today's society is characterized by quick technological developments and constant changes to our information environments. One of the biggest changes has been on our workplace environments where technological developments have automated work processes that were previously done by manual labour whilst new professions and work tasks have emerged in response to new methods of creating, sharing and using information. Information at Work: Information management in the workplace provides a comprehensive account of information in the modern workplace. It includes a set of chapters examining and reviewing the major concepts within workplace information, from over-arching themes of information cultures and ecologies, to strategic concerns of information management and governance, and to detailed accounts of questions and current debates. This book will be useful reading for researchers in Information Science and Information Management and students on related courses. It is also suitable to be used as an introductory text for those working in allied fields such as Management and Business Studies.